2022
DOI: 10.1017/s0033291722003610
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of technology-based interventions in psychosis: a systematic review and network meta-analysis

Abstract: Background Technology-based interventions (TBIs) are a useful approach when attempting to provide therapy to more patients with psychosis. Methods Randomized controlled trials of outcomes of TBIs v. face-to-face interventions in psychosis were identified in a systematic search conducted in PubMed/Ovid MEDLINE. Data were extracted independently by two researchers, and standardized mean changes were pooled using a three-level model and network meta-analysis. Results Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Given that recent meta-analyses show promise that digital technologies can effectively enhance care in psychosis treatment [ 12 ], it is of significance to explore the effectiveness of digital technologies on symptomatic and functional outcomes in concert with implementation outcomes. Assessing these outcomes in concert may shed light on the necessary next steps needed to bring the benefit of digital technologies to the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Given that recent meta-analyses show promise that digital technologies can effectively enhance care in psychosis treatment [ 12 ], it is of significance to explore the effectiveness of digital technologies on symptomatic and functional outcomes in concert with implementation outcomes. Assessing these outcomes in concert may shed light on the necessary next steps needed to bring the benefit of digital technologies to the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…eMental-health offers new possibilities for the study of voice-hearing and presents new treatment opportunities. Morales-Pillado et al (2023) found in their systematic review and network meta-analysis that digital interventions in general, including computer-and internet-based interventions, as a complement to treatment-as-usual (TAU), were on average slightly more effective in reducing psychotic symptoms than face-to-face interventions (g=0.16) in patients with psychosis. They concluded that digital interventions should be considered to be combined with TAU to patients with psychosis, since these interventions might be more accessible, flexible, and cost-effective than other face-to-face interventions.…”
Section: Digitization In Mental Health Carementioning
confidence: 99%